Using Application Usability Levels to support tracking the health of Heliophysics - Klenzing, Jeff; Halford, Alexa J.; Kellerman, Adam; Thompson, Barbara (Frontiers in Astronomy and Space Sciences, 2023)
The Application Usability Level (AUL) framework describes how a project advances from basic research to operation-ready applications. Here we expand upon the current project-level usage of AULs into a programmatic usage which can be used to help funding agencies track the health of the Heliophysics program. Examples are discussed throughout Heliophysics to show the utility of the AUL framework for describing the usability level of projects.